2012
DOI: 10.5223/pghn.2012.15.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Biological Therapy for Inflammatory Bowel Disease in Children

Abstract: The pathogenesis of inflammatory bowel diseases is not very well understood; it is currently thought to be caused by the interaction between genetic factors, environmental factors, intestinal microbes, and immune factors. Biological agents such as anti-tumor necrosis factor (anti-TNF) are widely being used as therapeutic agents. Infliximab, a chimeric monoclonal IgG1 antibody against tumor necrosis factor, has been demonstrated to have an effect in the induction and maintenance of remission in Crohn's disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…To our knowledge, this is the first study reported in Korea comparing the efficacies of 'top-down' infliximab treatment and 'step-up' treatment for pediatric CD over a 3-year period [10,27,28]. Although, relapse rate at 1 and 3 years was not significantly different, the relapse rate of the 'top-down' group was lower than that of the 'step-up' group.…”
Section: Discussionmentioning
confidence: 84%
“…To our knowledge, this is the first study reported in Korea comparing the efficacies of 'top-down' infliximab treatment and 'step-up' treatment for pediatric CD over a 3-year period [10,27,28]. Although, relapse rate at 1 and 3 years was not significantly different, the relapse rate of the 'top-down' group was lower than that of the 'step-up' group.…”
Section: Discussionmentioning
confidence: 84%
“…The paradigm of medical treatment for pediatric CD has changed with the emergence of effective biologic agents including infliximab and adalimumab [4]. Decreased surgery rate has been associated with successful use of immunomodulator or biologic agent [56].…”
Section: Introductionmentioning
confidence: 99%